PENGARUH KEPEMIMPINAN DAN MOTIVASI INTRINSIK TERHADAP KINERJA KARYAWAN KOPERASI PONDOK PESANTREN DARUSSALAM KECEMATAN KABUN KABPATEN ROKAN HULU - Zaky, Ahmad; -, Marzolina; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to explain the variable of Leadership and Intrinstic Motivation to the Employee Performance at Cooperative Boarding School Darussalam Kecamatan Kabun Rokan Hulu.The sampling method in this study using census methods, which all members of the population used as a sample, which amounted to 37 people. Data collection methods used were interviews, documentation and providing questionnaires to employees in accordance with the research conducted. Method of Multiple Regression Analysis using SPSS version 17.0The results from this study showed that simultaneously Leadership variabel and Intrinsic Motivation significantly influence the Employee performance at Cooperative Boarding School Darussalam Darussalam Kecamatan Kabun Rokan Hulu. While partially leadership variables influence the performance of the performance, and as well as for intrinsic motivation variable partially influence on employee performance. From the research that has been conducted, the leaders of cooperative boarding school Darussalam should be able to direct the employee to work independently, must have a high level of patience, to be able to adjust to the employee and also to have a good communicating. From intrinsic motivation, cooperative boarding school Darussalam must give feedback, critics and appreciation to employees in order to achieve good performance.Keywords: Leadership, Intrinsic Motivation, Performance